SISTEM INFORMASI PERAWATAN LOKOMOTIF BALAI YASA YOGYAKARTA BERBASIS ANDROID - Suparna -; Suraya -; Joko Triyono (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2016)
As the technology advances,the need for information is increasing. Smartphone is one of the technology that is often used by users to access the information, because the delivery of information via smartphones is simpler and easier.Smartphone withAndroid platform hasincreasedmost rapidly. The Android platform is growing very fast because it is open source so easily learned by anyone. Balai Yasa Yogyakarta is the only place in the locomotive maintenance and repair Java island owned by PT. Kereta Api Indonesia (Persero), and so we need an application that can provide information with an attractive appearance and can be accessed anywhere using a Smartphone. For this reason the author makes Androidbasedmobile application for locomotive maintenance information in Balai Yasa Yogyakarta is easy to use, effective and efficient. In making this mobile application software authors use Eclipse, JQuery Mobile, PHP and MySQL. And in the development of application systems using the waterfall model because the author of the work of the system is done in sequence or linear. With the Android based mobile application, users can find out a company profile, profile Yogyakarta workshop, information work programs, the concept of maintenance and locomotive maintenance mechanism, monitoring production data, production data and update the gallery locomotive. Based on the results of testing the system interface and functional testing systems, mobile applications are made to function as it should.